There’s (not) an App for that: situating smartphones, Excel and the techno-political interfaces and infrastructures of digital solutions for COVID-19 - Luke Heemsbergen; Catherine Bennett; Monique Mann (Humanities & Social Sciences Communications)
Abstract This paper focuses on the operational-infrastructural puzzles of mHealth via COVID-19 Contact Tracing Apps (CTA). Significant literature exists on user adoption of the platformisation of public health during the pandemic, but there has been limited consideration of how those responsible for implementing CTA design, deployment, and use of public health infrastructures did so. We redress this imbalance by exploring some of the politics and practicalities of offering CTA as technical ‘solutions’ to pandemic problems. Our work adds to previous comparative analyses of mHealth by drawing on data from key actors across government, industry, and civil society involved in designing and implementing CTA into public health across 5 jurisdictions: Australia, Canada, New Zealand, Singapore, and the United Kingdom. While CTA research often frames tensions around efficacy and adoption (e.g. privacy trade-off), we find hidden infrastructural tensions within a situation of political and technical constraints in the ‘back end’ of the platformisation of public health. The paper offers new insights to pandemic politics by shifting questions from digital contact tracing and pandemic surveillance interfaces to understanding CTA as infrastructures of public health. While CTA user-software interactions produce certain research questions, querying the infrastructural complexity of digital public health projects require and produce a different set of data and knowledge.